STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK KERIPIK PISANG 'MERASA' DI KABUPATEN TANJUNG JABUNG TIMUR - Marsya, Andi; Arif Musthofa, M.; Nurjali, Nurjali; Wandi (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This research is motivated by the high level of competition among entrepreneurs, especially traders, in attracting consumer attention in order to increase sales. One solution that can be applied is an effective and efficient marketing strategy. This marketing strategy focuses on four main elements known as the marketing mix, namely product, pricing, distribution policy, and promotion. The marketing mix has an important role in ensuring the survival of a business. However, in practice, marketing strategies are often still based on conventional economic principles. Therefore, this study aims to analyze the application of marketing strategies in increasing sales. This study uses a qualitative method with a type of field research. Primary data were obtained through interviews with business owners, employees, and prospective business successors, namely the children of the owner of the banana chips business